2009
DOI: 10.1128/iai.00665-09
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Regulates the Onset of Shiga Toxin 1-Induced Apoptosis in THP-1 Cells

Abstract: Shiga toxins (Stxs), which are proteins expressed by the enteric pathogens Shigella dysenteriae serotype 1 and some serotypes of Escherichia coli, are potent protein synthesis inhibitors. Stx-producing organisms cause bloody diarrhea with the potential to progress to acute renal failure and central nervous system complications. Studies using animal models of these diseases have shown that Stxs are major virulence factors, and purified toxins have been shown to be capable of killing many types of cells in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…The question whether depurination is necessary for RIP-induced cell death and not just a side effect is being controversially discussed [24][25][26][27][28]. Moreover, it is still not clear how depurination leads to cell death or why an inflammatory response is activated upon RIP treatment in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The question whether depurination is necessary for RIP-induced cell death and not just a side effect is being controversially discussed [24][25][26][27][28]. Moreover, it is still not clear how depurination leads to cell death or why an inflammatory response is activated upon RIP treatment in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Stx1 activates NF-B signaling in macrophage-like THP-1 cells, and TRAIL and DR5 gene expression is regulated by NF-B (20,48,54,64). DR5 expression is also regulated by CHOP (68), and Stx1 treatment of monocytic and macrophage-like THP-1 cells increases CHOP expression (33,36). Furthermore, we show here that RNAi knockdown of CHOP and DR5 expression partially protects macrophage-like cells from the cytotoxic action of Stx1.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts were collected and cleared by centrifugation at 15,000 ϫ g for 10 min. Cell lysates from monocytic THP-1 cells were prepared as previously described (33). Protein concentrations in each extract were determined using the Micro bicinchoninic acid (BCA) protein assay kit (Pierce, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that Stx2 cleaves procaspase 8 in HK-2 cells while Stx1 fails to do so. Stx-induced activation of caspase 8 may lead to the activation of the Bcl-2 protein family member BID, which in turn translocates to the mitochondria to facilitate mitochondrialmembrane depolarization and the release of mitochondrial intermembrane constituents into the cytoplasm (29). These events trigger the formation of the apoptosome and the activation of procaspase 9, and caspase 9 then activates caspase 3.…”
Section: Vol 79 2011 Response Of Hk-2 Cells To Shiga Toxin Types 1 mentioning
confidence: 99%